2014
DOI: 10.1111/bcpt.12323
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of Ascorbic Acid After High‐Dose Infusion in Prostate Cancer Patients: A Pharmacokinetic Evaluation

Abstract: Treatment with high-dose intravenous (IV) ascorbic acid (AA) is used in complementary and alternative medicine for various conditions including cancer. Cytotoxicity to cancer cell lines has been observed with millimolar concentrations of AA. Little is known about the pharmacokinetics of high-dose IV AA. The purpose of this study was to assess the basic kinetic variables in human beings over a relevant AA dosing interval for proper design of future clinical trials. Ten patients with metastatic prostate cancer w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
63
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(71 citation statements)
references
References 34 publications
5
63
0
1
Order By: Relevance
“…Compared to reported values in human clinical trials, our mouse data showed similar pharmacokinetics, with a rapid rise in plasma levels to within the mM range, followed by clearance with a half-life of $80 min. Similar values for plasma C max and T 1/2 , but lower AUC values than in human studies were observed, although comparisons are complicated by different doses (dosing by body surface area vs bolus dosing), infusion times (1 g/min vs bolus) and route (IV vs IP) [50,14]. One study of cancer patients with advanced disease showed that ascorbate infusion of 70-80 g/m 2 led to plasma levels of 10-20 mM lasting 5-6 h, but although eligibility for this study was dependent on a measurable biopsy, ascorbate levels were not measured in biopsy samples or in tumours postinfusion [14].…”
Section: Discussionsupporting
confidence: 57%
“…Compared to reported values in human clinical trials, our mouse data showed similar pharmacokinetics, with a rapid rise in plasma levels to within the mM range, followed by clearance with a half-life of $80 min. Similar values for plasma C max and T 1/2 , but lower AUC values than in human studies were observed, although comparisons are complicated by different doses (dosing by body surface area vs bolus dosing), infusion times (1 g/min vs bolus) and route (IV vs IP) [50,14]. One study of cancer patients with advanced disease showed that ascorbate infusion of 70-80 g/m 2 led to plasma levels of 10-20 mM lasting 5-6 h, but although eligibility for this study was dependent on a measurable biopsy, ascorbate levels were not measured in biopsy samples or in tumours postinfusion [14].…”
Section: Discussionsupporting
confidence: 57%
“…Peak plasma vitamin C concentrations occur immediately upon completion of a vitamin C infusion [24]. In our study, the vitamin C group had a higher plasma vitamin C concentration after surgery compared to the placebo group.…”
Section: Discussionmentioning
confidence: 61%
“…In our study, the vitamin C group had a higher plasma vitamin C concentration after surgery compared to the placebo group. The patients who received high dose (50 mg/kg) intravenous vitamin C at the start of surgery were apparently able to maintain higher plasma vitamin C concentrations throughout the surgery and in the early postoperative period, which may have been associated with decreased morphine consumption during the first 2 h after surgery and with the decreased pain scores at rest during first 24 h. While the single infusion of high dose vitamin C might have inhibited generation of ROS during surgery and contributed to reduced morphine consumption during the immediate postoperative period, the short half-life of the vitamin C does not support a sustained elevation of the plasma vitamin C concentration [24]. This could explain why there were no differences between groups in morphine consumption by 6 and 24 h postoperatively or in pain scores during cough at any time, and it suggests that a higher dose with a longer infusion time may be necessary to maintain adequate vitamin concentrations and sustained analgesic effects.…”
Section: Discussionmentioning
confidence: 99%
“…At infusion, the mean termination plasma AA concentration was 19.3 mM, and it was 15.1 mM after an additional 30 min. The detailed pharmacokinetic data of 10 participants have been published previously (12). The median baseline AA level was 54 µM (Q1–Q3: 45.6–73.5).…”
Section: Resultsmentioning
confidence: 99%
“…Patients received one weekly infusion of AA, as previously described (12). In brief, the initial dose was 5 g, followed by 30 g in week 2 and a final dose of 60 g in week 3.…”
Section: Methodsmentioning
confidence: 99%